Spirometric and anthropometric studies in normal children aged between 7 and 12 years - Singh, Rabindarjeet; Singh, Harbindarjeet; Seng, Quah Ban; Dharap, Amol Sharad (2001)
Spirometric data on 1183 healthy school children (551 boys and 632 girls) ranging in age from 7 to 12 years were analysed to derive predicted equations for (forced vital capacity, FEV 1 (forced expiratory volume in one second), FEF25-75% (maximal flow over the mid-portion of FVC), Vmax50% (flow rate after expiring 50% of FVC), and PEFR (peak expiratory flow rate). For all lung functions parameters, girls have lower values than boys. Using regression analysis, standing height appeared to be the most important predictor of pulmonary function across the age group. Regression equations constructed with logarithmically transfered dependent variables provided accurate predictions. Predicted FVC values derived from equation based on other population were higher than the observed mean in this study. This study therefore, reemphasises the need to be cautions when applying formulae derived from one population to another. Grossly erroneous conclusions may be reached unless predicted equations for lung parameters for a given are derived from studies base upon the same population group.